The Contribution of fruit from trees to improve household nutritional security in the context of deforestation in Cameroon - Tata epse Ngome, Precillia Ijang (Rhodes University, Faculty of Science, Department of Environmental Science, 2016)
Cameroon needs healthy citizens to archive emergence by 2035. Malnutrition and undernourishment is the highest burden in the World in recent times and a silent crisis facing most rural communities in forest areas of Cameroon. Its abstruseness makes extremely fragile political, social and economic planning to foster development in such areas. Therefore, it is time we bring appropriate understanding and new strategies on unpacking the complexities of food and nutritional security and define practical solutions to food insecurity. Working in the context of increasing deforestation, this thesis brings evidence on the situation of household food insecurity (FIS) access experience in forest areas which is not reported in current discussions at the national level. It further investigates the knowledge and awareness of households on the availability, accessibility, utilisation, vulnerability and consumption of nutrient rich food items using the example of fruits from trees. Thus, the aim of this research was to investigate strategies for addressing household FIS through increased domestic supply and consumption of fruits from trees in the context of deforestation in Cameroon. Data were collected through four rounds of structured interviews completed between August 2013 and October 2014. Analysis was done using simple citations and ordering, Principal Component Analysis (PCA), Likert scale, Ï‡2-test of association and Cramer's V coefficient to test the strength of the association and means and ANOVA. The HFIAS approach used to determine household FIS. Only 1% of the population were food secure and the moderately deforested zone showed the worst trends in food insecurity. Therefore, the effect of deforestation was nuanced. Diverse fruit trees were registered. Households said they required fruits only 2.4 Â± 1.5 times per week. Recently, the intake of 400 g of fruit per person per day for good health was announced as a priority of international recognition. However, households were not aware of the importance and frequency of fruit consumption with less than 50% of households eating fruits daily during the harvesting season. Fruit tree nurseries where scarce and seeds where obtained from local sources. Fruit tree diseases where rampant and up to 50% harvest lost was registered for some fruits species. This study has shown that food availability does not necessarily mean adequate food intake. Three opinions about fruit trees and the prevalence of food insecurity in Cameroon has been raised in this thesis. First, there is ineffectiveness in the eradication of FIS because even in agricultural conducive environments, hunger and food insecurity are still prevalent at high rates. Therefore, effective and efficient targeting of food insecured groups need to be promoted in all clusters of the population. Secondly, the national nutrition program is neglecting sensitisation on food consumption patterns and therefore people are not making use of nutrient rich foods even when this maybe found around their environments - taking the case of fruits from trees. Thus, very few people ate fruits and at irregular frequencies of consumption. Thus, there is need to design special campaign programs to promote the consumption of fruits from trees. Thirdly, the word-of-mouth or neighbour-to-neighbour dissemination approach on fruit trees planting has not been efficient across communities. As such nurseries where scarce and people obtained fruit trees plants from natural regeneration or found them on the field when establishing the field. Therefore, in this research, it is postulated that no matter the nature of efforts and level of intervention, what is certain is that addressing FIS requires effective targeting of the vulnerable population and the implementation of novel and practical approaches on promoting access to and consumption of fruits in the right frequencies. This research further revealed that poor eating habits was a problem and lack of knowledge about the frequency and intake of nutrient rich food was serious. For instance, people were not aware on the recommended frequency of fruit consumption and people ate infested fruit while reserving the healthy ones for sale. This is the trap of the food insecurity problem in some regions "“ knowledge about foods and ways of food utilisation. This is neither a problem of availability nor accessibility, but rather a problem of lack of knowledge and lack of sensitisation. From FAO reports on the state of food insecurity in the world and other studies of food intake in most developing nation, poor food consumption is a global problem in most poor regions and even in rich areas affected by obesity. Thus, there is a need to establish a high level policy framework maybe in the form of a convention or an intergovernmental panel at the level of the United Nations and/or the African Union on 'reducing malnutrition in all its forms (rates, drivers and consequences on human health and the environment)'. This structure will promote setting priorities, strategies, monitoring on peoples eating habits, setting nutritional standards, and principles and indicators for observing under nutrition, over nutrition and associated problems within all population strata.
Keywords: Uncatalogued